Towards relational dance history - Klimczyk, Wojciech (Relacyjność w kulturze i sztuce: Księga jubileuszowa Profesor Małgorzaty Leyko, 2025)
The article proposes a relational approach to dance history both as subject matter and academic discipline. In reference to Małgorzata Leyko’s seminal Dance in the Land of Utopia, which discusses the influence of Lebensreform ideas on modern-ist arts, most of all theatre and dance, the author postulates combining artistic and academic research even further than in modernism, in the process shaping culture of cooperation rather than competition, not only in the academic field. By looking at historical material, including contributions to dance theory and practice from Laban, Steiner, Jaques-Dalcroze and Schlemmer, studied at depth by Leyko, the article theorizes a practice-oriented approach to dance history prioritizing rela-tions over subjective positions and process over product. As such, the text devel-ops Leyko’s transpersonal, community-oriented way of conducting research, which is very effective in stimulating not only internal cooperation within the ac-ademic field but also between researchers and artists.